The Contribution of Corporate Social Responsibility (CSR) to The Achievement of the Millennium Development Goals (MDGs) in Mexico. - Moreno Lara, Alicia (2011)
The “sphere of influence” of the private sector is progressively moving beyond business-centric operations towards the promotion and protection of economic, civil, political, social, and cultural rights, mainstreaming the human right to development (UNGC, 2008). Human development is internationally promoted through global targets such as the Millennium Development Goals (MDGs) and locally endorsed according to national specific conditions. With the deadline to meet these global targets being 2015, (UN Millennium Project, 2000), the current paper examines the implementation of CSR practices that are deliberately or unintentionally driving the corporate engine towards the achievement of the MDGs. The research adopts the National Business Systems (NBS) theory as the conceptual framework to describe the characteristics of the Mexican business system, a key determinant of the coordination of national economic actors shaped by historical institutional frameworks. After a comprehensive analysis on the characteristics of the Mexican business system, a comprehensive description of the salience and development of Corporate Social Responsibility in Mexico is referred. Later on, the progress of the Millennium Development Goals in the country is widely described to subsequently develop an inclusive analysis of CSR practices promoting the accomplishment of the MDGs. The analysis entails 40 companies which CSR reports are thoroughly studied in order to withdraw the CSR practices that contribute to the achievement of the MDGs. The identified CSR actions are accordingly classified across the eight MDGs regarding the influence they have on accomplishing each of them. Finally, a profound account of the identified practices and their relation to the MDGs is detailed to conclude with a discussion that encompasses the characteristics of the Mexican Business System and the influence it has on the interplay between CSR and its contribution in achieving the MDGs.